Continuous-time random-walk approach to supercooled liquids: I. Different definitions of particle jumps and their consequences - Helfferich, Julian; Ziebert, Falko; Frey, S.; Meyer, H.; Farago, J.; Blumen, A.; Baschnagel, Jörg (Physical review. E, Statistical, nonlinear, and soft matter physics, 2014)
Single-particle trajectories in supercooled liquids display long periods of localization interrupted by “fast moves.” This observation suggests a modeling by a continuous-time random walk (CTRW). We perform molecular dynamics simulations of equilibrated short-chain polymer melts near the critical temperature of mode-coupling theory Tc and extract “moves” from the monomer trajectories. We show that not all moves comply with the conditions of a CTRW. Strong forward-backward correlations are found in the supercooled state. A refinement procedure is suggested to exclude these moves from the analysis. We discuss the repercussions of the refinement on the jump-length and waiting-time distributions as well as on characteristic time scales, such as the average waiting time (“exchange time”) and the average time for the first move (“persistence time”). The refinement modifies the temperature (T) dependence of these time scales. For instance, the average waiting time changes from an Arrhenius-type to a Vogel-Fulcher-type T dependence. We discuss this observation in the context of the bifurcation of the α process and (Johari) β process found in many glass-forming materials to occur near Tc. Our analysis lays the foundation for a study of the jump-length and waiting-time distributions, their temperature and chain-length dependencies, and the modeling of the monomer dynamics by a CTRW approach in the companion paper [J. Helfferich et al., Phys. Rev. E 89, 042604 (2014)].
Gesehen am 27.09.2022